KKN-PkM Berdampak: Transformasi Pembelajaran SD melalui Game-Based Learning - Sri Nuraini; Wahyu Sri Ambar Arum; Taufik Rihatno; Muhammad Iqro Zakaria; Muhammad Rasyied Saleh; Arif Teguh Laksono; Dede Rianto; Rizki Irawan; Arita Marini (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The urgency of empowering the teachers at SDN Tanah Tinggi 03, Central Jakarta, through a Community Service (PkM) activity integrated with the Student Community Service Program (KKN), lies in the implementation of game-based learning aimed at enhancing learning effectiveness and student engagement. The main objective of this teacher empowerment program is to improve the pedagogical skills and creativity of SDN Tanah Tinggi 03 teachers in managing physical education learning through game-based learning. The approach taken to address the challenges faced by the school involved providing training and guidance on the application of game-based learning in classroom instruction. The PkM KKN activity was conducted on Monday, July 21, 2025, at SDN Tanah Tinggi 03. As a result of the program, teachers at SDN Tanah Tinggi 03 demonstrated improved competencies in applying game-based learning, enabling them to integrate educational games effectively into their physical education teaching strategies.